Exploring Shariah Audit Training Impact on Shariah Audit Understanding by Malaysian Students - Muhammad Iqmal Hisham Kamaruddin; Mustafa Mohd Hanefah; Zurina Shafii; Supiah Salleh; Nurazalia Zakaria (Human Resource Management Academic Research Society, 2024)
Indexed by ERA